Lire dedans et en dehors des bocaux du réalisme magique et du Southern Gothic : allers-retours des littératures des Amériques - Santos Chinchilla, Carlos Humberto (Verbum – Analecta Neolatina, 2025)
Certain literatures of the Americas have been misinterpreted. Due to this misunderstanding, notions such as magical realism and Southern Gothic are today anchored in the collective imagination of a large part of the reading public, whether specialist or amateur. Is it possible to question these interpretations despite their consecration and popularity? This work explains why it is necessary. Existing labels and other alternatives to describe the region’s literature will be studied using a comparative and decolonial approach. This paper will both reaffirm the different realities of the Americas and suggests a new way of qualifying these literatures with greater accuracy and justice: multitransrealism.